أثر العرف في معايير ال كفاءة في النكاح: دراسة مقاصدية = The effect of custom in the criteria of competence in marriage: a Maqasidic study - Al-Marri, Ali Mubarak; Sitiris, Miszairi; Arif, Arif Ali (IIUM Press, International Islamic University Malaysia, 2019)
This research addresses some of the deviant customs which affect the determination of the criteria of competence in marriage as a result of variations of this determination according to the variation of time and place. The customs that are intended for research in this study are three. First, defects related to outward appearance in the suitor and its effects on his competence; second, suitor’s belonging to a state other than that of the fiancée; and third, his wealth or poverty and its effect on his competence. The research concluded that competence criteria are not fixed. Rather, they vary with the variation of situations. Moreover, the customs mentioned earlier have certain serious and harmful effects such as women committing prohibited things, their delinquency of temptation and sinful acts, and the spread of spinsterhood in the society. Also, the determination of competence in marriage in an unnatural manner is harmful to the family and the entire society due to its contradiction to the Shariah’s objectives of preserving the religion and progeny.